Protein localisation by electron microscopy reveals the architecture of the yeast spliceosomal B complex. (18th November 2015) - Rigo, Norbert; Sun, Chengfu; Fabrizio, Patrizia; Kastner, Berthold; Lührmann, Reinhard
Abstract: The spliceosome assembles on a pre‐mRNA intron by binding of five snRNPs and numerous proteins, leading to the formation of the pre‐catalytic B complex. While the general morphology of the B complex is known, the spatial arrangement of proteins and snRNP subunits within it remain to be elucidated. To shed light on the architecture of the yeast B complex, we immuno‐labelled selected proteins and located them by negative‐stain electron microscopy. The B complex exhibited a triangular shape with main body, head and neck domains. We located the U5 snRNP components Brr2 at the top and Prp8 and Snu114 in the centre of the main body. We found several U2 SF3a (Prp9 and Prp11) and SF3b (Hsh155 and Cus1) proteins in the head domain and two U4/U6 snRNP proteins (Prp3 and Lsm4) in the neck domain that connects the main body with the head. Thus, we could assign distinct domains of the B complex to the respective snRNPs and provide the first detailed picture of the subunit architecture and protein arrangements of the B complex. Synopsis: By combining immuno‐labelling and negative‐stain EM this study reveals the subunit architecture of the spliceosomal B complex and assigns individual snRNP components to distinct domains. The main axis of the B complex harbours the U5 snRNP. The B complex neck domain contains the U4/U6 di‐snRNP. The U2 snRNP and the RES complex are located in the head domain of the B complex. The U4/U6·U5 tri‐snRNP is structurally well‐preserved in the open conformation. Abstract : By combining immuno‐labelling and negative‐stain EM this study reveals the subunit architecture of the spliceosomal B complex and assigns individual snRNP components to distinct domains.